2016
DOI: 10.3746/pnf.2016.21.4.317
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Eicosapentaenoic Acid and Docosahexaenoic Acid on Mitochondrial DNA Replication and PGC-1α Gene Expression in C2C12Muscle Cells

Abstract: Mitochondrial biogenesis is a complex process requiring coordinated expression of nuclear and mitochondrial genomes. The peroxisome proliferator-activated receptor gamma co-activator 1-alpha (PGC-1α) is a key regulator of mitochondrial biogenesis, and it controls mitochondrial DNA (mtDNA) replication within diverse tissues, including muscle tissue. The aim of this study was to investigate the effects of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) on mtDNA copy number and PGC-1α promoter activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 28 publications
3
18
0
5
Order By: Relevance
“…19 Consistently, DHA was reported to upregulate mRNA levels of Pgc1α and stimulate PGC1α promoter activity in a doseand time-dependent manner in C2C12 muscle cells. 20 These results suggest that the anti-hepatosteatotic effect of DHA in our NAFLD model is partly mediated by the modulation of mitochondrial biogenesis and promotion of TAG export but not the reduction of hepatic lipogenesis. The protective effect of DHA on hepatic steatosis in vivo was also supported by in vitro data.…”
Section: Discussionmentioning
confidence: 52%
“…19 Consistently, DHA was reported to upregulate mRNA levels of Pgc1α and stimulate PGC1α promoter activity in a doseand time-dependent manner in C2C12 muscle cells. 20 These results suggest that the anti-hepatosteatotic effect of DHA in our NAFLD model is partly mediated by the modulation of mitochondrial biogenesis and promotion of TAG export but not the reduction of hepatic lipogenesis. The protective effect of DHA on hepatic steatosis in vivo was also supported by in vitro data.…”
Section: Discussionmentioning
confidence: 52%
“…It was reported that the n − 3 PUFAs could cause higher oxidation levels of mitochondrial fatty acids in the myocardium ( 19 22 ). EPA and DHA individually increase mitochondrial biosynthesis in skeletal muscle stem cells ( 23 25 ). Therefore, we hypothesize that EPA and DHA treatment on myofibroblasts (C2C12 cells) may affect the myogenesis and adipogenesis via metabolic changes in mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…Like PPARs, the peroxisome proliferator-activated receptor gamma co-activator 1-alpha (PGC-1α) is also capable of repressing the transcriptional activity of NF-kB lowering inflammation in muscle cells [ 90 ]. In differentiated C2C12 myotubes, n-3 PUFAs have been found to increase the expression of PGC-1α in a dose and time dependent manner with 50 μM for 24 h having the greatest effect [ 91 ]. PGC-1α is also indirectly involved in regulating the expression of mitochondrial DNA (mtDNA) by increasing the transcription of mitochondrial transcription factor A (Tfam) and nuclear respiratory factor 1 (NRF1) [ 92 ].…”
Section: The Beneficial Effects Of N-3 Pufas In Skeletal Musclementioning
confidence: 99%
“…PGC-1α is also indirectly involved in regulating the expression of mitochondrial DNA (mtDNA) by increasing the transcription of mitochondrial transcription factor A (Tfam) and nuclear respiratory factor 1 (NRF1) [ 92 ]. In fully formed myotubes, the expression of both Tfam and NRF1 have been shown to increase following both EPA and DHA treatment [ 91 ]. Moreover, overexpressing PGC-1α in C2C12 cells has been shown to promote differentiation and increase the expression of MyoD and Myogenin, however, it remains to be seen whether n-3 PUFAs can elicit similar responses in both PGC-1α and MRF expression during differentiation [ 93 ].…”
Section: The Beneficial Effects Of N-3 Pufas In Skeletal Musclementioning
confidence: 99%